Economic Empowerment through Making Hand Sanitizer and Implementing Healthy Lifestyles in Covid-19 Pandemic - Nurul Hidayah; Yeasy Agustina Sari; Suryawahyuni Latief; Suhono, Suhono (Yayasan Payungi Smart Madani, 2021)
Making product Hand sanitizer and implementing a clean and healthy lifestyle were an effort to break the chain of the spread of Covid-19. The making of hand sanitizer made from alcohol has been recognized as being able to kill viruses. For example Alcohol, H2O2 (Hydrogen Peroxide), Glycerol / Glycerin, and Aquades / Distilled Water. This new normal situation must be balanced with a healthy lifestyle. The aim of this assistance was to conduct training in making hand sanitizer in order to improve the economy and the application of healthy living during the Covid-19 pandemic. The researchers used ABCD (Asset Community Based Development) method, with stages; Discovery, Dream, Design, Define, and Destiny. Through this method, the discovery of assets and potentials leads to the provision of activities in the form of training and mentoring to produce hand sanitizer product. This economic assistance activity has an impact on the availability of hand sanitizer that were quite used by residents, and in marketing using online media which has a significant impact on residents.